IBU HAMIL KEKURANGAN ENERGI KRONIS (KEK) BERISIKO MELAHIRKAN BAYI BERAT BADAN LAHIR RENDAH (BBLR) DI PUSKESMAS GARUNG KABUPATEN WONOSOBO - Siti Alifah Nur'aini; Wahyu Pujiastuti; Sri Widatiningsih (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2016)
Malnutrition in pregnant women can lead to birth with low birth weight. Based on the data in Garung Health Centerin 2013, the overall number of infants with low birth weight (LBW) infants was 71 from 890 deliveries, while pregnant women who suffer from Chronic Energy Deficiency(CED) as many as 85 people.This research is ananalytic survey with case-control approach, the population in this study were alllow birth weight babies in health centers Garung, Wonosobo district in 2013 as many as 71 babies. Sample retrieval techniques used in this study is simple random sampling technique, as many as 63 babies, consisted of 63 low birth weight infants and 63 infants not low birth weight as a control group.The results showed the significance valueof p 0.05 is 0.000, indicating a link pregnant women with chronic energy deficiency with low birth weight. RR: 14.712 which means pregnant women with Chronic Energy Deficiency (CED) 14.712 times greater risk of having a baby with low birth weight (LBW). The analysis results are also obtained chi-square value is 0.000. The statement indicates that the variables studied are strong relationships.The results of this reseach are expected for pregnant women to antenatal care their self as early as can to know their nutrition condition. For the midwives in order to do examination of the upper arm circle continuesly and give illumination about the nutrition of pregnant women,for further research to examine factors associated with low birth weight (LBW) factors other than pregnant women with chronic energy deficiency (CED), for example, the incidence of anemia in pregnant women, the incidence of bleeding and maternal parity.